(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis of Coffee Export from East Nusa Tenggara Province to the Global Market. This study aims to analyze the factors influencing the volume of coffee exports from East Nusa Tenggara (NTT) Province to the global market. The research utilizes annual time series data from 2004 to 2023 and is analyzed using multiple linear regression based on the Ordinary Least Squares (OLS) method with the assistance of EViews 13 software. The variables analyzed include land area, coffee production, and the ratio of global coffee prices to domestic coffee prices. The model estimation results show that all independent variables simultaneously have a significant effect on the volume of coffee exports from NTT. However, partially, only coffee production has a positive and significant influence on export volume, while land area and the global-to-domestic coffee price ratio do not show significant effects. These findings indicate that increasing coffee production is a key factor in promoting coffee exports from NTT to the global market. Therefore, efforts to improve coffee productivity should be a top priority, including technical assistance for farmers, crop rejuvenation, and strengthening of farmer institutions. Meanwhile, the statistically insignificant effects of land area and price differentials suggest that additional strategies are needed to optimize the use of existing land and enhance farmers’ access to market information. Local governments are expected to provide sustainable support to improve productivity and efficiency in the coffee sector so that the export potential of this commodity can be better realized in the international market.